(3JbjjO Gdeged hJejjR GdeTcds - (3CHh Ydj GdMSjf Hf eMeO Hf CMeO GdZSGfj GdCfOdSj, GdLjGfj,J (B498 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg GHf YjSi Hf YHO GdQMef Hf eGgGf GdHZOGOi Yf CHj HcQ CMeO Hf eMeO Hf jMji GdCTbQ Gdabjg Ydi ePgH GdTGaYi s
(3BNQgG (B:s
(3hgPg MedI bO CJi YdjgG GdJaSjQ ajeG JbOe ef cJGHfG gPG hGdMeO ddg BNQ cJGH GdJYQja HTjhN GdHNGQi QMeg Gddg jJdhg Cf TGA Gddg cJGH GdCdbGH s
(3BNQ GdLRA GdSGHY fbUs
(3GdfSNI HgG MhGTs
(3HgG CKQ JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs